Study on The Effect of Polymerised Palm Oil on The Fatigue Performance of Hot Mix Asphalt - Vijayakumar, Kishankumar (Universiti Teknologi PETRONAS, 2020)
One of the main factors that lead to the development of a nation’s socio-economy is contributed by proper roadways and pavements. It has facilitated the smooth transport of goods for import and export, thus allowing economic advancement of any entity. As such, road pavements play an important for such transport vehicles in order for them to travel safely and comfortably. Maintenance of the pavements can contribute to this aspect, as ensuring the surface of the pavements are smooth and durable that can take on the traffic loads that are imposed repeatedly on it as time goes on. Numerous researches have been done to study how does the pavement fails, in the aspect of its fatigue performance.